Personalized Medicine on Muscinous Ovarian Cancer - Effendy Fila; Antonius Puja Agung (Syntax Corporation Indonesia, 2024)
Ovarian cancer (OC), ranking third among gynecological cancers, poses a significant health concern with the worst prognosis and highest mortality rate. The global incidence, as per 2018 data, reached 295,414 cases, constituting 3.4% of women's cancer cases. The prevalence has notably risen in Asian countries, including Singapore and Indonesia. This report highlights two cases from Dr. M. Djamil, emphasizing the importance of personalized medicine (PM) in treating OC. PM, leveraging genomic information, aids in tailoring treatments for individual patients. The standard treatment involves cytoreductive surgical debulking and platinum-based chemotherapy. Notably, PM has shown promise in addressing specific genetic mutations, such as BRCA1 and BRCA2, prevalent in breast and ovarian tumors, enabling more targeted therapeutic approaches and enhancing treatment outcomes.